PENGGUNAAN MULTIMEDIA DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS X SMA NEGERI 5 BURU KECAMATAN LILIALY KABUPATEN BURU - Tiarni Soamole; Samad Umarella; Saddam Husein (Kuttab: Jurnal Ilmiah Mahasiswa, 2021)
Abstract: This study aims to find out how the use of multimedia in improving students' learning motivation in Islamic Religious Education subjects in the Classroom X SMA Negeri 5 Buru as well as supporting factors and inhibition of the use of multimedia. This research was conducted in SMA Negeri 5 Buru District Lilialy Kabupaten Buru, from September 1, 2020 to October 1, 2020. This research is a qualitative descriptive research with data collection techniques in the form of observations, interviews and documentation. The collected data is then analyzed qualitatively including: data collection, data reduction, data display and verification and affirmation of conclusions. The results showed that the use of multimedia can increase students' learning motivation in Islamic Religious Education subjects in the classroom X SMA Negeri 5 Buru, where students appear to focus on following the learning process, recording the subject matter, and are happy with the learning using multimedia, students easily explain or answer the teacher's questions PAI boldly and actively in the learning process. Supporting factors and inhibition factors of multimedia use in increasing students' learning motivation in Islamic Religious Education subjects in the Classroom X SMA Negeri 5 Buru among others, for supporting factors, namely the availability of leptop and computer, infokus, electricity, clean school walls, clean classrooms, and the ability of PAI teachers who are very good in integrating concepts with multimedia in the learning process as well as the availability of special classrooms designed for learning activities using multimedia infokus. As for the inhibition factor is infokus available only one, so it will be constrained when used by other teachers, then electricity is often out and internet access is often sluggish. Keywords: Multimedia, student learning motivation, Islamic Religious Education Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana penggunaan multimedia dalam meningkatkan motivasi belajar siswa pada mata pelajaran Pendidikan Agama Islam di Kelas X SMA Negeri 5 Buru serta faktor pendukung dan penghambat penggunaan multimedia tersebut..Penelitian ini dilaksanakan di SMA Negeri 5 Buru Kecamatan Lilialy Kabupaten Buru, mulai dari tanggal 1 September 2020 sampai dengan 1 Oktober 2020.. Penelitian ini merupakan penelitian deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, wawancara dan dokumentasi. Data yang terkumpul kemudian dianalisis secara kualitatif meliputi: pengumpulan data, reduksi data, display data dan verifikasi dan penegasan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan multimedia dapat meningkatkan motivasi belajar siswa pada mata pelajaran Pendidikan Agama Islam di kelas X SMA Negeri 5 Buru, dimana siswa terlihat mereka fokus mengikuti proses pembelajaran, mencatat materi pelajaran, dan senang dengan pembelajaran menggunakan multimedia, siswa dengan mudah menjelaskan atau menjawab pertanyaan guru PAI dengan berani dan aktif dalam proses pembelajaran. Faktor pendukung dan faktor penghambat penggunaan multimedia dalam meningkatkan motivasi belajar siswa pada mata pelajaran Pendidikan Agama Islam di Kelas X SMA Negeri 5 Buru antara lain untuk faktor pendukung yakni tersedianya leptop dan komputer, infokus, listrik, dinding sekolah yang bersih, ruang kelas yang bersih, dan kemampuan guru PAI yang sangat baik dalam mengintegrasikan konsep dengan multimedia dalam proses pembelajaran serta tersedianya ruang kelas khusus yang didesain untuk kegiatan pembelajaran menggunakan multimedia infokus. Sementara untuk faktor penghambatnya adalah infokus yang tersedia hanya satu, sehingga akan terkendala apabila digunakan oleh guru yang lain, kemudian listrik sering padam dan akses internet yang sering lamban. Kata kunci: Multimedia, motivasi belajar siswa, Pendidikan Agama Islam